Hubungan panjang-bobot dan faktor kondisi ikan baronang (Siganus guttatus, Bloch 1787) di Perairan Sei Carang Kota Tanjungpinang, Indonesia - Yuri Indriyani; Susiana Susiana; Rochmady Rochmady (Sangia Publishing, 2020)
Sei Carang waters are baronang fish habitat (Siganus guttatus). The research was to determine the length-weight correlationship and condition factors of baronang fish (S. guttatus) in Sei Carang. Sampling of baronang fish (S. guttatus) in two months (September-Oktober 2019) is taken once a week based on fishing activities and water conditions. Length-weight correlationship of female and male baronang fish (S. guttatus) were W = 2,0895E-05L2,9575 and W = 1,30073E-05L3,0424 respectively, based on this value show that female and male baronang fish (S. guttatus) in Sei Carang have isometric growth patterns (b = 3). Condition factors of female and male baronang fish (S. guttatus) were 1,735 and 1,633 respectively.